Investigating Effects of Testing Parameters on Frictional Heating of UHMWPE by Taguchi Method - Sagbas, B.; Durakbasa, M. N. (POLISH ACAD SCIENCES INST PHYSICS, 2014)
Frictional heating makes detrimental effects on surrounding tissue and lubricant around the artificial hip joint. For reduction of this thermal damage, testing parameters and their effects were investigated by using the Taguchi method and analysis of variance. Ultra high molecular weight polyethylene (UHAIWPE) acetabular liners and CoCrMo femoral head artificial hip joint components were used as samples. Frictional heating measurements of the joints were carried out on a custom made hip joint friction experimental setup. Surface dimples in different sizes were machined on the inner surface of acetabular insert samples. The tests were conducted under different loading conditions with different testing time. Bovine calf serum was used as lubricant with different amount of third body wear particles in it. Temperature rise in acetabular and femoral component was recorded with embedded thermocouples. The experimental results demonstrated that the surface dimples were the major parameter on frictional heating, followed by applied load, amount of third body particles and time. The optimal combination of the testing parameters was predicted and validated by doing experiments.
Keywords: TOTAL HIP IMPLANTS; SURFACE; WEAR; Physics